2020
DOI: 10.1371/journal.pone.0227505
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic interleukin 11 expression causes cross-tissue fibro-inflammation and an inflammatory bowel phenotype in mice

Abstract: Interleukin 11 (IL11) is a profibrotic cytokine, secreted by myofibroblasts and damaged epithelial cells. Smooth muscle cells (SMCs) also secrete IL11 under pathological conditions and express the IL11 receptor. Here we examined the effects of SMC-specific, conditional expression of murine IL11 in a transgenic mouse (Il11 SMC). Within days of transgene activation, Il11 SMC mice developed loose stools and progressive bleeding and rectal prolapse, which was associated with a 65% mortality by two weeks. The bowel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…After 5 days of tamoxifen treatment, there was a ~56% reduction in IL11RA protein levels in whole lung lysates from CKO mice, which is expected given the predominant expression of Il11ra1 in Col1a2 +ve fibroblasts ( Figure 1B and S2B). 19,20 Immunofluorescence staining revealed a greatly decreased expression of IL11RA ( Figure 1C) and we detected a ~70% reduction of Il11ra1 mRNA expression in primary fibroblasts isolated from the lungs of CKO mice when compared to control mice ( Figure 1D). Confirming fibroblast-specific deletion, tamoxifen treatment did not affect the expression of Il11ra1 in a Col1a2 -ve cell type from the lungs of CKO mice.…”
Section: Generation and Validation Of Fibroblast-specific Il11ra1 Kmentioning
confidence: 79%
“…After 5 days of tamoxifen treatment, there was a ~56% reduction in IL11RA protein levels in whole lung lysates from CKO mice, which is expected given the predominant expression of Il11ra1 in Col1a2 +ve fibroblasts ( Figure 1B and S2B). 19,20 Immunofluorescence staining revealed a greatly decreased expression of IL11RA ( Figure 1C) and we detected a ~70% reduction of Il11ra1 mRNA expression in primary fibroblasts isolated from the lungs of CKO mice when compared to control mice ( Figure 1D). Confirming fibroblast-specific deletion, tamoxifen treatment did not affect the expression of Il11ra1 in a Col1a2 -ve cell type from the lungs of CKO mice.…”
Section: Generation and Validation Of Fibroblast-specific Il11ra1 Kmentioning
confidence: 79%
“…To study the effects of IL11 on VSMCs in vivo, we crossed Rosa26 Il11/ + transgenic mice 14 with mice that express tamoxifen (TAM)-inducible Cre recombinase driven by the myosin heavy chain 11 ( Myh11 ) promoter 29 . This model allows SMC-specific Il11 overexpression in an inducible manner in adult mice (referred to here as Il11 -Tg mice) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…23 While we know much less about IL11, it has emerged as an important pro-fibrotic factor across organs and, more recently, as a hepatotoxin. 5,[8][9][10][11] IL6R and IL11RA expression in hepatocytes and hepatic stellate cells IL6, originally termed B cell growth/stimulatory factor II (BSF2), 24 was initially shown to stimulate acute phase response from HepG2 cells and rat hepatocytes. 25 Subsequent studies showed that IL6 can be produced from and act on the liver and IL6 is a well-established and important determinant of the acute phase response, which involves secretion of CRP, serum amyloid A, hepcidin, among other factors from hepatocytes.…”
Section: Il6 and Il11different Children From The Same Familymentioning
confidence: 99%
“…7 Only very recently, have experiments shown a central role for endogenous and species-matched IL11 in the pathology of fibroinflammatory diseases such as inflammatory bowel disease (IBD), cardiorenal and lung fibrosis, and acute and chronic liver disease. 5,[8][9][10][11] In this review, we examine the roles IL6 and IL11 in the liver and discuss the therapeutic opportunities these cytokines may provide for liver disease. While the older literature proposed these two cytokines have overlapping and redundant roles in the liver, we discuss recent data that challenges longheld assumptions.…”
Section: Introductionmentioning
confidence: 99%